Evaluation of radioadaptive response induced in CHO-K1 cells in a non-traditional model - Grillo, Claudia Alejandra (2009)
Purpose: The present study was designed to evaluate the effects of sequential exposures to low doses of gamma-radiation that induce a radioadaptive response to a later high-dose of radiation in CHO-K1 cells. Materials and methods: Cells were cultured in four dilution cycles and grown to confluency. Radiation treatment was performed once per cycle with 0.1 Gy gamma-rays. After the last radiation period (chronic radiation) the culture was irradiated with a higher dose (1 Gy). Each cell culture was immediately divided into two fractions: one of them was used to carry out the comet assay and the other for the structural chromosome aberration test. In the first fraction, genotoxic damage was evaluated by degree of damage in 300 cells per experimental point. The second assay was performed with 400 cells per treatment. The statistical analysis was carried out using the 2-test. Results: Results from these assays demonstrated a genotoxic effect for both the adaptive and acute treatments (p0.001). The comet assay showed a significant increase in damage for the combined treatment when compared with 1 Gy treatment (p0.001). The frequency of chromosomal aberrations (CA) was lower for the combined treatment than for that using the highest radiation dose. Conclusions: These results suggest the possible induction of a radioadaptive response after the sequential exposure to very low doses of radiation. The finding of decreased cytogenetic damage after one cell cycle and not immediately after radiation could indicate the eventual potentiation of repair mechanisms.